Uncovering deep-rooted conflicts: the role of psychoanalytic psychotherapy in treating athletes' social media-related psychological distress - Piepiora, Paweł Adam; Petre, Ligiana Mihaela; Vveinhardt, Jolita (Frontiers in Sports and Active Living, 2024)
The use of social media by athletes can support them in difficult moments, but it can also become a source of negative emotions and psychological distress. This perspective critically examines psychoanalytic psychotherapy as a method for restoring athletes' psychological well-being after experiencing negative effects from social media use. The paper characterizes the key elements of psychoanalytic psychotherapy relevant to athletes, discusses the role of the psychoanalytic psychotherapist in working with athletes and describes the specifics of the psychoanalytic therapeutic process in this context. The potential advantages of psychoanalytic approaches over cognitive-behavioral methods are examined in treating the psychological impacts of problematic social media use among athletes. The analysis suggests that hate speech and negative online interactions can activate athletes' unprocessed life experiences rooted in early developmental stages. Psychoanalytic psychotherapy may offer a particularly effective method for restoring athletes' psychological wellbeing in such cases by addressing deep-rooted intrapsychic conflicts. However, a comprehensive approach integrating multiple therapeutic modalities is recommended to address the complex challenges athletes face in the digital age. This perspective acknowledges limitations in current research and suggest directions for future studies to develop and validate tailored interventions for athletes grappling with social media-related psychological distress.